Time dependent alterations of serum matrix metalloproteinase-1 and metalloproteinase-1 tissue inhibitor after successful reperfusion of acute myocardial infarction. Issue 3 (September 1997) - Hirohata, S.; Kusachi, S.; Murakami, M.; Murakami, T.; Sano, I.; Watanabe, T.; Komatsubara, I.; Kondo, J.; Tsuji, T.
Abstract : OBJECTIVE: To test the hypothesis that changes in serum matrix metalloproteinase-1 (MMP-1) and tissue inhibitors of metalloproteinase-1 (TIMP-1) after acute myocardial infarction reflect extracellular matrix remodelling and the infarct healing process. PATIENTS: 13 consecutive patients with their first acute myocardial infarction who underwent successful reperfusion. METHODS: Blood was sampled on the day of admission, and on days 2, 3, 4, 5, 7, 14, and 28. Serum MMP-1 and TIMP-1 were measured by one step sandwich enzyme immunoassay. Left ventricular volume indices were determined by left ventriculography performed four weeks after the infarct. RESULTS: Serum concentrations of both MMP-1 and TIMP-1 changed over time. The average serum MMP-1 was more than 1 SD below the mean control values during the initial four days, increased thereafter, reaching a peak concentration around day 14, and then returned to the middle control range. Negative correlations with left ventricular end systolic volume index and positive correlations with left ventricular ejection fraction were obtained for serum MMP-1 on day 5, when it began to rise, and for the magnitude of rise in MMP-1 on day 5 compared to admission. Serum TIMP-1 at admission was more than 1 SD below the mean control value, and increased gradually thereafter, reaching a peak on around day 14. Negative correlations with left ventricular end systolic volume index and positive correlations with left ventricular ejection fraction were obtained for serum TIMP-1 on days 5 and 7, and for the magnitude of rise in TIMP-1 on days 5 and 7 compared to admission. CONCLUSIONS: Both MMP-1 and TIMP-1 showed significant time dependent alteration after acute myocardial infarction. Thus MMP-1 and TIMP-1 may provide useful information in evaluating the healing process as it affects left ventricular remodelling after acute myocardial infarction.